Fresh Beef Consumption Patterns and Socioeconomic Determinants in Jalingo Emirate, Nigeria - Ja'afar-Furo, Muhammad R.; Abubakar, Aliyu; Abdullahi, Aishatu (Universitas Negeri Gorontalo, 2024)
The paper assessed the fresh beef products consumer preference and consumption pattern in Jalingo Emirate communities of Nigeria. A sample of 300 respondents was drawn through random sampling method, and analysed by the use of descriptive statistics and multiple regression analysis. Findings showed that majority of the fresh beef consumers were males within the age range of 20-50 years, and mostly singles. A larger proportion (49.00%) of the beef consumers had secondary school certificates. Occupationally, 34.00% of the respondents were traders earning between N21,000 and N70,000 only. Majority (77.33%) of the respondents consumed less than 2.00kg of beef monthly in the area. Most (74.00%) of the beef consumers eat the commodity at home with 40.00% of them consuming it 1-3 times weekly. The major determinants of fresh beef and its products consumption were age, monthly expenditure on substitutes, monthly income, price of beef, frequency of consumption and gender. The most experienced challenges for the beef consumers include outrageous cost of beef, unhygienic method of preparation and unwholesomeness of the beef. Institutions intending to minimise these constraints should assiduously work toward resolving these raised issues in the communities of the Emirate.